THE EFFECT OF WORD SEARCH PUZZLE GAME IN TEACHING VOCABULARY TO THE SIXTH GRADE STUDENTS OF SDN KOLPAJUNG II - Dian Ratih Megawati (Universitas Madura, 2019)
In this study there are two problems of study. The first is Is there any effect of Word Search Puzzle Game in teaching vocabulary to the sixth grade students of SDN Kolpajung II. The second how significant is the use of Word Search Puzzle Game gives effect in the teaching vocabulary to the sixth grade students of SDN Kolpajung II.The population of this research is all of students at the sixth grade of SDN Kolpajung II. While the sample of this research is the sixth grade students of SDN Kolpajung II. There are 29 students of sixth grade at SDN Kolpajung II. In this research uses quantitative approach, while research design that is used in this research is pre-experimental. Research instruments that used in this study are test and documentation. Test is used to measure students vocabulary. While documentation is used to support and complete the data such as lesson plan, pre-test and post-test scores, photo, etc. The result of this research is there was significance effect of Word Search Puzzle Game in teaching vocabulary to the sixth grade student at SDN Kolpajung II because the t-value was higher than t-table in significance alpha 5% The score of t-value in this research was 2,05 and the score of t-table was 10.865 in level significance 5% with degree of freedom 28 ( 10.865>2,05 ). From these results, it is suggested to the English teachers to use an appropriate technique in teaching English especially in teaching vocabulary, in this case using Word Search Puzzle Game since Word Search Puzzle Game was gave positive effect in teaching vocabulary. It is also expected for further researchers to continue this research on the other vocabulary items.